Data from: Areal differences in depth cue integration between monkey and human - Armendariz, Marcelo; Ban, Hiroshi; Welchman, Andrew E; Vanduffel, Wim (Dryad, 2019)
Electrophysiological evidence suggested primarily the involvement of area
MT in depth cue integration in macaques, as opposed to human imaging data
pinpointing area V3B/KO. To clarify this conundrum, we decoded monkey fMRI
responses evoked by stimuli signaling near or far depths defined by
binocular disparity, relative motion and their combination, and we
compared results with those from an identical experiment previously
performed in humans.Responses in macaque area MT are more discriminable
when two cues concurrently signal depth, and information provided by one
cue is diagnostic of depth indicated by the other. This suggests that
monkey area MT computes fusion of disparity and motion depth signals,
exactly as shown for human area V3B/KO. Hence, these data reconcile
previously reported discrepancies between depth processing in human and
monkey by showing the involvement of the dorsal stream in depth cue
integration using the same technique, despite the engagement of different
regions.
data describing fig 1-8 and sfig 1-12data.zip
Keywords: monkey; Depth; Integration; human